Welfare Services from a Minority Perspective. Explaining Satisfaction with Language-Based Welfare Services among Swedish-Speaking Finns - Himmelroos, Staffan; Vento, Isak; von Schoultz, Åsa (Minorités linguistiques et société / Linguistic Minorities and Society, 2021)
This article explores perceptions of welfare services from the perspective of a linguistic minority, the Finland-Swedes. Since Finland has an extensive universal welfare system and is an officially bilingual country, the relatively small Swedish-speaking numerical minority has equal rights to welfare provision in their mother tongue. This provides an analytically promising case, as expectations toward the Finnish welfare system are high, while delivering quality language-based welfare services to minorities can be challenging. We hypothesize that attitudes regarding language-based welfare service are guided by either rational self-interest, i.e. language skills, or ingroup identity. Our analyses are based on a survey among a random sample of Swedish-speaking Finns in the winter of 2018-2019. We found that the attitudes toward language-based welfare services were guided by both self-interest and identity, but their impact depended on whether respondents were asked about their specific evaluation of, or general desire for, language-based welfare services.